159 Safety and Efficacy of Lurasidone in Children and Adolescents with Bipolar Depression: Results from a 2-Year Open-label Extension Study. (April 2020) - DelBello, Melissa P.; Goldman, Robert; Tocco, Michael; Deng, Ling; Pikalov, Andrei
Abstract: Background: Bipolar I disorder frequently has an early onset, with an estimated prevalence rate of 1.8% in pediatric populations. Early onset is associated with a high degree of chronicity; however, limited data are available on the long-term efficacy of drug therapies in pediatric populations. The aim of the current study was to evaluate the long-term safety and efficacy of lurasidone in children and adolescents with bipolar depression. Method: Patients 10-17 years with bipolar I depression were randomized to 6 weeks of double-blind (DB) treatment with lurasidone or placebo. Patients who completed the study were eligible to enroll in a 2-year, open-label (OL) extension study in which patients were continued on flexibly-dosed lurasidone (20-80 mg/d; LUR-LUR) or switched from placebo to lurasidone (PBO-LUR). The primary efficacy measure was the Children's Depression Rating Scale, Revised (CDRS-R); response was defined as ≥50% reduction from DB baseline in the CDRS-R total score. Results: A total of 306 patients completed the 6-week DB study and entered the extension study; 195 (63.7%) completed 52 weeks, and 168 (54.9%) completed 104 weeks of treatment. Mean CDRS-R total score at DB baseline was 59.4 in patients treated with lurasidone, and 58.7 in patients treated with placebo; and mean CDRS-R total score at OL baseline (after 6 weeks of DB treatment) was 36.6 in the LUR-LUR group and 41.9 in the PBO-LUR group. For the total sample of patients in the OL study, mean change (from OL baseline) in the CDRS-R score was -13.4 at week 52 and -16.4 at week 104; and responder rates were 51.0% at OL baseline (64.5% for LUR-LUR; 36.9% for PBO-LUR), 88.4% at week 52, and 91.1% at week 104. During OL treatment with lurasidone, 31 patients (10.1%) discontinued due to an adverse event. The most commonly reported events were headache (23.9%), nausea (16.4%), and somnolence (9.8%). OL treatment with lurasidone was associated with few effects on metabolic parameters or prolactin. Mean change from DB baseline in weight was +4.25 kg at week 52 (vs. an expected weight gain of 3.76 kg based on CDC normative data), and +6.75 kg at week 104 (vs. CDC expected weight gain of 6.67 kg). Conclusion: Two years of treatment with lurasidone in children and adolescents with bipolar depression was generally well-tolerated, with relatively low rates of study discontinuation. Lurasidone treatment was associated with few effects on weight, metabolic parameters, and prolactin. Patients also continued to experience improvement in depressive symptoms during long-term treatment with lurasidone. Clinicaltrials.gov identifier: NCT01914393 Funding Acknowledgements: Supported by funding from Sunovion Pharmaceuticals Inc.